2001
DOI: 10.1073/pnas.121005298
|View full text |Cite
|
Sign up to set email alerts
|

The synaptic activity of HsDmc1, a human recombination protein specific to meiosis

Abstract: Human Dmc1 protein, a meiosis-specific homolog of Escherichia coli RecA protein, has previously been shown to promote DNA homologous pairing and strand-exchange reactions that are qualitatively similar to those of RecA protein and Rad51. Human and yeast Rad51 proteins each form a nucleoprotein filament that is very similar to the filament formed by RecA protein. However, recent studies failed to find a similar filament made by Dmc1 but showed instead that this protein forms octameric rings and stacks of rings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 45 publications
(73 reference statements)
9
51
0
Order By: Relevance
“…Rate constants of the reaction between DNAs with mismatches are consistent with this idea, because it is reported that mismatches (i) reduce the rate of the pairing step; (ii) increase the off rate during the pairing step; and (iii) reduce the rate of subsequent strand exchange (57). Recent studies employing oligonucleotides with varying GC-content as recombination substrates revealed that both the E. coli RecA and its human homologs Rad51 and Dmc1 rely on A:T base pairs for recognition of homology (58)(59)(60).…”
Section: Homologous Recombination In Phage T4supporting
confidence: 57%
“…Rate constants of the reaction between DNAs with mismatches are consistent with this idea, because it is reported that mismatches (i) reduce the rate of the pairing step; (ii) increase the off rate during the pairing step; and (iii) reduce the rate of subsequent strand exchange (57). Recent studies employing oligonucleotides with varying GC-content as recombination substrates revealed that both the E. coli RecA and its human homologs Rad51 and Dmc1 rely on A:T base pairs for recognition of homology (58)(59)(60).…”
Section: Homologous Recombination In Phage T4supporting
confidence: 57%
“…4a). The lack of helical filaments was surprising because Dmc1 has high sequence conservation with RecA-related proteins and because biophysical studies revealed that Dmc1 and Rad51 recognise homology in the same way 32 . It was suggested that rings were an artefact caused by lack of essential cofactors 32 , but models for ring-based DNA strand exchange were also proposed 33 .…”
Section: Dmc1-mediated Dna Strand Exchangementioning
confidence: 99%
“…Phylogenetic analysis indicates that DMC1 is a RecA-like protein [60]. DMC1 homologs have been identified in a wide range of organisms, including budding and fission yeast, mammals, plants, and fungi [61][62][63][64][65][66][67][68][69][70]. In the budding yeast, the severity of dmc1 mutants varies among different strains.…”
Section: Dsb Processing and Function Of Reca Proteinsmentioning
confidence: 99%